The Organizational Improvements of Catering in the Case of the Radisson Blu Resort Restaurant in Split - Bogdanović, Mario; Maračić, Stefanija (Oeconomica Jadertina, 2017)
The essence of the catering industry is providing food and beverages services. The food and beverages department provides the food and beverages in the hotel industry, with its restaurant being the most visible part where the food and beverages supply and demand takes place. The researching of this organizational segment is important because it contributes to the understanding and improvement of theorganizational efficacy of the food and beverage department, in particular the restaurant units of the catering organizations. The aim of this paper is to explore the organization of work within the food and beverage department in the Hotel Radisson Blu Resort in Split. The proposed research evolves around the problems of the organization of work of a specific restaurant Fig & Leaf located in the Radisson Blue Resort Split Hotel. The research was conducted by means of questionnaire that included all the employees of the restaurant (N=20). Certain problem areas have been identified in the restaurant’s organization of work: a) a sub-optimal number of employees; b) multiple chain of commands; c) problems of sub-optimal organizational structures in the work of the restaurant; d) problems regarding certain aspects of the organizational culture of the restaurant relating to team work, participatory decision-making, inter-personal trust. For the diagnosed problems in the organization of the restaurant organizational solutions were offered aimed at improving management. This way of solving the organizational sub-optimality can be generally applied within the restaurant business.
Keywords: hotel industry; food and beverage department; organization of work; restaurant management; organizational consulting; catering industry